Intervención de kinesiología en individuos con sobrepeso u obesidad: análisis de la composición del cuerpo y calidad de vida - Leichsenring Silva, Fabiano (2019)
As one of the leading causes of preventable death, obesity is a condition of excessive fat that accompanies a constellation of other morbidities that in parallel increases risk of heart disease and/or cancer. The body composition assessment has achieved proven improvement with regular practice of physical activity. This research seeks to answerhow a program of primary intervention can influence body composition and quality of life on overweighted/obeseindividuals, with the main objective to analyze body composition in overweight individuals. This work seeks totailor the use of physical exercise together with seven natural agents. The sample consisted of individuals aged between 18 and 30 years, who underwent anthropometric, functional and quality of life evaluations. The interventionprotocol was conducted during eight weeks, resulting in reduction of body fat percentage, body weight reduction,reduced BMI and improved quality of life